NTUplace4h: A Novel Routability-Driven Placement Algorithm for Hierarchical Mixed-Size Circuit Designs - Hsu, Meng-Kai; Chen, Yi-Fang; Huang, Chau-Chin; Chou, Sheng; Lin, Tzu-Hen; Chen, Tung-Chieh; Chang, Yao-Wen (IEEE transactions on computer-aided design of integrated circuits and systems, 2014)
A wirelength-driven placer without considering routability could introduce irresolvable routing-congested placements. Therefore, it is desirable to develop an effective routability-driven placer for modern mixed-size designs employing hierarchical methodologies for faster turnaround time. In this paper, we propose a novel routability-driven analytical placement algorithm for hierarchical mixed-size circuit designs. This paper presents a novel design hierarchy identification technique to effectively identify design hierarchies and guide placement for better wirelength and routability. The proposed algorithm optimizes routability from four major aspects: 1) narrow channel handling; 2) pin density; 3) routing overflow optimization; and 4) net congestion optimization. Routability-driven legalization and detailed placement are also proposed to further optimize routing congestion. Compared with the participating teams for the 2012 ICCAD Design Hierarchy Aware Routability-driven Placement Contest, our placer can achieve the best quality (both the average overflow and wirelength) and the best overall score (by additionally considering running time).